Exploring the Factors that Influence University Selection: Insights from College Students - Nour Nasser Mohammed Al Tamimi; Omayma Mohammed Said Al Mashrafi; Mohammed Muneerali Thottoli (Profesional Muda Cendekia Publishing, 2023)
Purpose: Due to the significant pace and divergence in higher education, choosing the university that best suits the student's goals is crucial. The university's ranking may also influence students' decisions in choosing. Universities face rising competition from other institutions, such as new or internationally emerging universities, colleges, and even organizational training courses, on a national and global level. Thus, this study aims to identify the broad categories of determinants in the information required of college students who expect and need when selecting a university to continue their studies. Methodology: Using questionnaires, research data was gathered from Omani college students. They addressed their requirements, expectations, and understanding of choosing a university. Using the SEM-PLS software, these data were thematically examined. Findings: The study found that factors like infrastructure and location of the university had little influence on students' decisions. But it was found that the university reputation was significantly influenced by choosing a university. The findings imply that criteria like location and infrastructure may be less significant than a university's reputation, which is crucial in decision-making among college students